Physicochemical characteristics of rice bran sourdough fermented with Lactobacillus plantarum for breadmaking - Mat Gani, Hanis Syazwani (2014)
A general growing awareness of healthy lifestyle increased the interest of the food industry in the market of high fiber products. Rice bran, an agro-byproduct obtained from outer rice layers, could offer a new variety of baked goods with high fiber content. However, bran supplementation usually can cause severe problems to the quality of final products. Thus, supplementation with bran requires changes in processing techniques for the production of baked goods with good consumer quality. One of the techniques being employed is fermentation and this study was carried out to optimize the fermentation conditions of rice bran sourdough. This was then followed by evaluation of the rice bran sourdough functionality. Rice bran used in this study contained 10.9% moisture, 16.1% fat, 12.7% protein, 8.8% ash, 22.4% insoluble dietary fiber, 1.3% soluble dietary fiber and 27.8% carbohydrate. The use of lactic acid bacteria (LAB) and yeast starter cultures in the fermentation process resulted in slight differences among the fermentative end product characteristics of the sourdough. These characteristics were highly influenced by the LAB strains used. Lactobacillus plantarum was better than Lactobacillus brevis and Lactobacillus sanfranciscencis at producing the desired pH, total titratable acidity (TTA), organic acids, fermentation quotient and soluble sugars required in sourdough preparation. A response surface methodology (RSM) and central composite design (CCD) were employed to obtain the optimum fermentation conditions for obtaining acidic properties and antioxidant phenolic compounds in rice bran sourdough incorporated with Lactobacillus plantarum. The acidity values found showed that the fermentation temperature and time at 33°C and 12.5 hours, respectively, were able to produce optimum pH (pH 3.5 to 4.5) and total titratable acidity (16 to 22 ml of 0.1M NaOH). Total phenolic compounds increased in parallel with increasing fermentation temperature and time. Rice bran sourdough gave breads with significantly higher loaf specific volume (4.65cm3/g) and crumb softness (3.54) compared to rice bran bread and wheat bran sourdough bread. Sourdough was able to maintain the freshness and prolong shelf life of the bread. Supplementation of the bread dough with bran darkened the final product. Rice bran sourdough bread got the lowest score, in terms of overall acceptance, when compared to wheat bran sourdough, rice bran, wheat bran and control (no bran) breads in sensory evaluations.